2014
DOI: 10.1371/journal.pntd.0003064
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Orientia tsutsugamushi and Inflammatory Responses in a Murine Model of Scrub Typhus

Abstract: Central aspects in the pathogenesis of scrub typhus, an infection caused by Orientia (O.) tsutsugamushi, have remained obscure. Its organ and cellular tropism are poorly understood.The purpose of this study was to analyze the kinetics of bacterial dissemination and associated inflammatory responses in infected tissues in an experimental scrub typhus mouse model, following infection with the human pathogenic strain Karp. We provide a thorough analysis of O. tsutsugamushi infection in inbred Balb/c mice using fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(138 citation statements)
references
References 66 publications
12
125
1
Order By: Relevance
“…Thus, they concluded that BALT and pleuritic infiltrates could contribute to early bacterial degradation, while solitary infected cells in the parenchyma may have escaped immunosurveillance during the initial phase of infection. Importantly, no bacteria were found in CD31-positive endothelial cells despite a close spatial relationship in this study [25].…”
Section: Cellular Tropism Is the Key To Dissemination And Pathogenesiscontrasting
confidence: 51%
“…Thus, they concluded that BALT and pleuritic infiltrates could contribute to early bacterial degradation, while solitary infected cells in the parenchyma may have escaped immunosurveillance during the initial phase of infection. Importantly, no bacteria were found in CD31-positive endothelial cells despite a close spatial relationship in this study [25].…”
Section: Cellular Tropism Is the Key To Dissemination And Pathogenesiscontrasting
confidence: 51%
“…TLRs are crucial mediators of resistance to many infections and mediate resistance by limiting pathogen growth. We thus investigated whether TLR2 is required for survival and the control of O. tsutsugamushi Karp growth during the acute infection phase, using our recently developed mouse footpad infection model, which closely approximates natural inoculation via the dermis (16). All wild-type and tlr2 Ϫ/Ϫ mice survived the acute infection phase until day 21 p.i.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the influence of TLR2 on host resistance to O. tsutsugamushi, we first used an experimental mouse model based on the dermal inoculation route via the hind footpad (16). In this model, all tlr2 Ϫ/Ϫ mice survived and were able to control bacterial growth as well as wild-type mice did, as shown by the kinetics of the bacterial loads from draining lymph nodes, spleen, and lung.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations